Hubungan Antara Kekuatan Otot Lengan Terhadap Kemampuan Open Smash Dalam Permainan Bola Voli Unit Kegiatan Mahasiswa Universitas Musamus - Hendra Jondry Hiskya (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
This study aims to determine the relationship between arm muscle strength and the ability to smash open members of the Unmus Volleyball Student Activity Unit. The subjects of this study were members of the Unmus Volleyball Student Activity Unit. The research subjects amounted to 20 people. Retrieval of data using a test, with an arm muscle strength test instrument with a spring scale (spring scale) as a measuring tool. The unit of measure is kilogram (kg). This test has been standardized with known validity, using content validity and a reliability of 0.92. Open smash ability test with a volleyball smash ability test for UNMUS Volleyball Student UKM. The final test score for each player is the score obtained in 10 smashes. The data analysis technique uses simple regression and correlation analysis through the normality and linearity prerequisite tests. The results of the study showed that there was no significant relationship between arm muscle strength and the ability to smash open Unmus volleyball UKM members. Because the value of r count = 0.160 in the relationship between arm muscle strength and the ability to open smash is smaller than the price of r table = 0.337. But the strength of the arm muscles contributes to the ability of the open smash by 2.5%.